Hybrids offcially released/registered for commecialization - CGIAR Research Program on Maize (2018)
Among the released/registered hybrids two are take-up by producers, including RCRMH-2 released by UAS-Raichur, India, sub-licensed to Mahyco, India and commercialized in Karnataka & Maharashtra states of India with commercial name “MRM-4070” and Lall-454 is registered by LALL Seeds Odisha, India and commercialize with same name in Odisha, India..